Optimasi Persediaan Perencanaan dan Pengendalian Biaya Air Minum Kemasan di CV. Dinasti 611 - Chandrahadinata, Dody; Cahyadi, Ujang; Ramdani, Uji (Jurnal Kalibrasi, 2023)
CV Dynasty is a trading company engaged in the distribution of bottled drinking water. The CV Dynasty 611 company collaborates with suppliers to supply bottled drinking water. In carrying out its business processes, this company is often hampered by inventory management. This can be seen from the accumulation of goods and frequent placing of orders with suppliers, as well as problems in fulfilling products to consumers. So a method is needed to solve problems in inventory management and optimize storage and ordering costs and avoid buildup in the warehouse. So the inventory management method was chosen Economic order quantity, silver meal heuristic and Min – max method. These three methods are inventory management methods which are expected to be able to solve problems that occur at the CV Dynasty 611 company. The EOQ method produces an order frequency of 19 times, safety stock of 102 crates, ROP of 118 crates with a total inventory cost of IDR 36,925,824 and inventory cost efficiency of IDR 2,226,976 with an inventory cost efficiency percentage of 6%. Meanwhile, using the silver meal heuristic method produces an ordering frequency of 12 times a year, safety stock 156, ROP 114, total inventory costs IDR 8,881088 with inventory cost efficiency IDR 30,271,712 with a percentage of 77%. Meanwhile, using the min - max method produces an order frequency of 13 times in one year with a safety stock of 102 crates, ROP 114 crates with a total inventory cost of 34,071,456 with an inventory cost efficiency of IDR 5,081,341 with an inventory cost efficiency percentage of 13%. Therefore, it is recommended that companies use the silver meal heuristic method to optimize inventory costs.